2012
DOI: 10.1111/j.1601-0825.2012.01973.x
|View full text |Cite
|
Sign up to set email alerts
|

IL1 gene polymorphisms in relation to external apical root resorption concurrent with orthodontia

Abstract: Although no significant role of IL1A (-889C/T) and IL1B (+3953C/T) variants in EARR was confirmed, IL1RN VNTR may be associated with EARR, especially in girls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
2
11

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(54 citation statements)
references
References 46 publications
1
40
2
11
Order By: Relevance
“…27,28 Interleukin 1 is one of the first cytokines implicated in inflammation of the vessel wall during tooth movement, affecting leucocyte recruitment and transmigration. [29][30][31][32][33] Closely connected to this, the function of interleukin 1 is antagonized by the IL1ra protein encoded in the IL1RN gene, wherein specific sequence variants have been associated with an increased predisposition to suffer OIEARR. 11,32 In this connection, subjects homozygous for the T allele of the IL1RN variant studied here may be prone to imbalances in cytokine levels on the IL1ra/IL1b axis during orthodontic tooth movement, which may be associated with a decreased bone remodeling rate that directly influences the subsequent increase in radicular stress.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…27,28 Interleukin 1 is one of the first cytokines implicated in inflammation of the vessel wall during tooth movement, affecting leucocyte recruitment and transmigration. [29][30][31][32][33] Closely connected to this, the function of interleukin 1 is antagonized by the IL1ra protein encoded in the IL1RN gene, wherein specific sequence variants have been associated with an increased predisposition to suffer OIEARR. 11,32 In this connection, subjects homozygous for the T allele of the IL1RN variant studied here may be prone to imbalances in cytokine levels on the IL1ra/IL1b axis during orthodontic tooth movement, which may be associated with a decreased bone remodeling rate that directly influences the subsequent increase in radicular stress.…”
Section: Discussionmentioning
confidence: 99%
“…[29][30][31][32][33] Closely connected to this, the function of interleukin 1 is antagonized by the IL1ra protein encoded in the IL1RN gene, wherein specific sequence variants have been associated with an increased predisposition to suffer OIEARR. 11,32 In this connection, subjects homozygous for the T allele of the IL1RN variant studied here may be prone to imbalances in cytokine levels on the IL1ra/IL1b axis during orthodontic tooth movement, which may be associated with a decreased bone remodeling rate that directly influences the subsequent increase in radicular stress. Failure to identify the DNA information of each subject means failing to include the risk inherent in certain patient genotypes, which leads to misinterpreting the observed results of the appliance's effect on OIEARR.…”
Section: Discussionmentioning
confidence: 99%
“…Del mismo modo Linhartova et al (2013) no logró establecer asociación entre el polimorfismo del gen IL-1B y la RRE en pacientes con ortodoncia.…”
Section: Discussionunclassified
“…The results of the present review suggest that although some authors have reported that genetic polymorphism may play a role in EARR, [4][5][6][7][8][9][20][21][22][23]24 others have not supported this association. [25][26] Published orthodontic investigations in gene studies have seldom adhered to the STREGA or any genetic guidelines. As a result, the study may suffer from methodological inaccuracies, which can introduce bias.…”
Section: Summary Of Evidencementioning
confidence: 99%